Phenol–Chloroform DNA Extraction for DNA Amplification from Personal Items - Ernanto, Aditya Rahman; Khasanah, Dinda Amaliyatul; Aldirahayu, Yunita; Setiyaningrum, Rizki; Iswara, Arya (UI Scholars Hub, 2026)
This study examined the feasibility of extracting DNA from various personal items using the phenol–chloroform–isoamyl alcohol (PCIA) method. A towel, collared shirt, toothbrush, shower puff, comb, hair tie, and buccal swabs were analyzed. The quality of the DNA extraction, along with DNA concentration, purity, and suitability for multiplex PCR amplification, were evaluated. The shower puff exhibited the highest DNA concentration (68.35 ng/µL), whereas the collared shirt yielded the lowest (26.43 ng/µL). All samples exhibited good DNA purity (A260 nm/A280 nm ranging from 1.827 to 1.985), emphasizing the potential of this method for forensic analysis. Factors influencing DNA concentration included material composition, surface area, and exposure to bodily fluids. The results highlight the importance of understanding material-specific characteristics to optimize DNA extraction protocols. Buccal swabs served as reliable controls, suggesting their potential use in personal item DNA extraction studies. The successful extraction of DNA from personal items holds promise for enhancing the scope of DNA analysis in criminal investigations. The PCIA method is useful for DNA extraction from personal items and may serve as an alternative when standard methods cannot be used.